Roy Friedman scrapbook - Friedman, Roy.
Scrapbook titled "An odyssey of the Friedman brothers" created by Roy Friedman about his father, Max Friedman, and uncle, Leon Friedman. Contains text by Roy Friedman and news clippings, photographs, and ephemera relating to Leon and Max Friedman's work promoting aviation and organizing air shows in China, Japan, and the U.S., circa 1910 to 1918; and as automobile dealers in Shanghai, China, 1919-1940. Subjects include pioneer woman aviator, Katherine Stinson; China Motors and Star Garage, Shanghai, China; and the Hupmobile
Leon Friedman and Max Friedman: promoters of early aviation and later, car dealers in Shanghai, China.
Collection material in English.
Keywords: Friedman, Leon, -- -1961.; Friedman, Max, -- -1942.; Stinson, Katherine, -- 1891-1977.; China Motors; Star Garage; Aeronautics; Air pilots; Air shows -- China; Air shows -- Japan; Air shows -- United States; Automobile dealers -- China -- Shanghai; Automobiles; Hupp automobile; Women air pilots; Shanghai (China) -- Commerce; Businessmen